KETEGUHAN REKAT DAN EMISI FORMALDEHIDA PAPAN LAMINA ROTAN MENGGUNAKAN PEREKAT TANIN FORMALDEHIDA - Rohmah Pari; Abdurachman; Adi Santoso (BRIN Publishing, 2019)
Composite products made of rattan have a decorative value and potentially can be developed for current market demand. Rattan laminated board is expected to perform effective as a substitution material for wooden furniture. The aim of this research is to determine technology of making laminated rattan board from large rattan species which having diameter of more than 30 mm using phenol based adhesive from organic resources, i.e. bark (mangium, mahoni) and merbau sawdust. The laminated rattan board sizing of 1.5 cm x 7.5 cm x 90 cm were made of five layers which spreaded on one side of the surface and hot pressed with 10 kg/cm2 specific pressure for three hours. Testing of rattan laminated board products includes bonding strength and formaldehyde emissions, and also the bonding strength value of samples from the National Rattan Innovation Center (PIRNas) as a comparison. Results show that bonding strength and formaldehyde emissions of the rattan laminated board was influenced by interaction type of tannin-formaldehyde, pressing temperature, and glue spread. The best quality adhesive performance of rattan boards was obtained on the use of tannin-formaldehyde mangium resin with formaldehyde emissions with a glue spread of 200 g/m2 surfaces and 100oC pressing temperature, with formaldehyde emmision within the safe limits. Approximately 28% of the experimental rattan laminated boards possessed bonding strength which exceeds bonding strength value of the PIRNas board, which used synthetic resin based on the imported phenolic adhesive.